Experimental Analysis of Resonance Behavior in a Mechanical Vibrating Beam - Muhammad Fachri Rizki; Asraf Aulia Yondra; Mohammad Syaifullah Yusuf; Angles Sihotang; Fardin Hasibuan (Universitas Riau Kepulauan, 2025)
This paper presents an experimental analysis of resonance behavior in a mechanical vibrating beam. A cantilever beam made of aluminum was subjected to forced vibrations using a shaker, and the frequency response was measured with an accelerometer. Resonance frequencies for the first three modes were determined and compared with theoretical predictions based on Euler-Bernoulli beam theory. The experimental results showed excellent agreement with theoretical values, with errors less than 1%, validating the approach. This study underscores the importance of understanding resonance in mechanical structures to prevent failures due to excessive vibrations.